A biogenic approach for green synthesis of silver nanoparticles using extract of Foeniculum vulgare and its activity against Staphylococcus aureus and Escherichia coli - SHITAL BONDE (Smujo International, 2011)
Abstract. Bonde S. 2011. A biogenic approach for green synthesis of silver nanoparticles using extract of Foeniculum vulgare and its activity against Staphylococcus aureus and Escherichia coli. Nusantara Bioscience 3: 59-63. We report green synthesis of silver nanoparticles from extract of Foeniculum vulgare (fennel, saunf). The synthesis of silver nanoparticles was detected by changing color from green to brown after treatment with AgNO3 (1mM) and the UV-visible spectrophotometer analysis showed the absorbance peak at about 427 nm, which indicates the synthesis of silver nanoparticles. Nanoparticle Tracking and Analysis (NTA) by LM-20 was used for multi-parameter analysis, allowing for characterization of particle size and particle distribution of silver nanoparticles synthesized from extract of F. vulgare. NTA revealed the polydispersed nanoparticles in the range of 18-83 nm. Phytosynthesized silver nanoparticles showed antibacterial activity against the Staphylococcus aureus (ATCC-25923) and Escherichia coli (ATCC-39403). The silver nanoparticles also demonstrated remarkable antibacterial activity against two human pathogenic bacteria when used in combination with commercially available antibiotics. The bactericidal activity of the standard antibiotics was significantly enhanced in presence of silver nanoparticles against pathogenic bacteria, viz. E. coli-JM-103 (ATCC-39403) and S. aureus (ATCC-25923). Silver nanoparticles in combination with vancomycin showed maximum activity against E. coli (increase in fold area 5.76. and followed by S. aureus (1.08) and Gentamicin showed the maximum activity S. aureus (2.6) while E. coli (0.96). The approach of phytosynthesized silver nanoparticles using F. vulgare appears to be cost-efficient, eco-friendly and easy alternative to conventional methods of synthesis.